Upaya Guru Pendidikan Agama Islam dalam Membina Perilaku Keagamaan Siswa : Studi Kasus di Kelas XI IPA SMA NU Juntinyuat Indramayu - Fatimatuz Zahra; Umi Habibah; Suci Muzfirah (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
This study aimed to explore the efforts of Islamic Religious Education (PAI) teachers in fostering religious behavior among Class XI IPA students at SMA NU Juntinyuat Indramayu. Using a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and documentation, involving purposively selected informants until data saturation was reached. The research found that students generally exhibit positive religious behaviors, including active participation in daily congregational prayers and Quranic recitation. However, a segment of students remains disengaged due to various internal and external factors. To address this, teachers employ comprehensive strategies, including habituation programs (e.g., morning communal remembrance, congregational prayers), cognitive understanding through religious sermons and motivation, and consistent role modeling. Supporting factors for these efforts include strong institutional cooperation, structured religious programs, and adequate facilities. Conversely, challenges encompass individual student differences, low self-discipline, lack of intrinsic motivation, and limited parental involvement. The findings suggest the critical need for integrated, collaborative strategies involving schools, families, and the broader community to sustainably enhance students' religious behavior and moral character.